Marine actinobacteria metabolites: unlocking new treatments for acne vulgaris - De La Hoz-Romo, María Clara; Díaz, Luis; Gómez-León, Javier; Quintero, Marynes; Villamil, Luisa (Frontiers in Microbiology, 2025)
Marine-derived actinobacteria isolated from sponge Cliona varians and soft coral Eunicea fusca were screened for antibacterial activity against acne-related bacteria, specifically Staphylococcus epidermidis ATCC 14990, methicillin-resistant Staphylococcus aureus ATCC BAA44, and Cutibacterium acnes ATCC 6919. Cytotoxicity assays were performed on human dermal fibroblast (HDFa) and keratinocyte (HaCaT) cell lines to assess the safety profile of the extracts. Chemical characterization was conducted using high-performance liquid chromatography coupled with tandem mass spectrometry (HPLC–MS/MS). Among the extracts, six derived from Kocuria sp., Rhodococcus sp., Nocardia sp., Micrococcus sp., and Streptomyces sp. demonstrated significant antibacterial activity. Notably, extract Z9.216 from Kocuria sp. exhibited the highest efficacy, inhibiting S. epidermidis by 68%, S. aureus by 93%, and C. acnes by 98.7% at a concentration of 0.003 mg/mL, which was comparable to the standard antibiotics erythromycin and vancomycin, while maintaining over 90% cell viability in both HDFa and HaCaT cell lines. Untargeted metabolomic analysis suggested that antibacterial activity might be associated with compounds from the chemical families of alkaloids, terpenoids, and fatty acids, among others. These findings highlight the therapeutic potential of marine actinobacteria in underexplored environments as a promising strategy for treating acne vulgaris, a chronic inflammatory skin condition.